2006
DOI: 10.1029/2005jb004251
|View full text |Cite
|
Sign up to set email alerts
|

Elasticity of MgO to 11 GPa with an independent absolute pressure scale: Implications for pressure calibration

Abstract: [1] P and S wave velocities and unit cell parameters (density) of MgO are measured simultaneously up to 11 GPa using combined ultrasonic interferometry and in situ X-ray diffraction techniques. The elastic bulk and shear moduli as well as their pressure derivatives are obtained by fitting the measured velocity and density data to the third-order finite strain equations, yielding K 0S = 163.5(11) GPa, K 0 0S = 4.20(10), G 0 = 129.8(6) GPa, and G 0 0 = 2.42(6), independent of pressure. These properties are subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
40
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 44 publications
11
40
0
1
Order By: Relevance
“…Lower mantle thermodynamics and rheology are thus largely controlled by periclase and its Fe-bearing analogue (ferropericlase) [16,[107][108][109][110]. (14) and (15) Calculated results of this work are compared to selected experimental data obtained by hydrostatic or quasi-hydrostatic compression in the diamond-anvil cell [90][91][92][93] and ultrasonic measurements [94][95][96][97]. The results of semi-empirical assessments [98,100], other ab initio LDA [59], GGA [61] and empirically-corrected GGA [101] calculations and MD simulations [60,84] are also shown for comparison.…”
Section: P-v-t Equation Of State (Eos)mentioning
confidence: 99%
See 1 more Smart Citation
“…Lower mantle thermodynamics and rheology are thus largely controlled by periclase and its Fe-bearing analogue (ferropericlase) [16,[107][108][109][110]. (14) and (15) Calculated results of this work are compared to selected experimental data obtained by hydrostatic or quasi-hydrostatic compression in the diamond-anvil cell [90][91][92][93] and ultrasonic measurements [94][95][96][97]. The results of semi-empirical assessments [98,100], other ab initio LDA [59], GGA [61] and empirically-corrected GGA [101] calculations and MD simulations [60,84] are also shown for comparison.…”
Section: P-v-t Equation Of State (Eos)mentioning
confidence: 99%
“…Figure 7 and Table 4 show the results obtained for the P-V-T equation of state of periclase, as compared to different kinds of experimental data (i.e., static compression in the diamond-anvil cell, ultrasonic measurements, etc.) [89][90][91][92][93][94][95][96][97], semi-empirical modelling of experimental data [98][99][100] and other DFT [59,61,101] and MD [60,84] calculations. The EOS of MgO has been calculated according to Equation (15) in a range of conditions compatible with those realized in the Earth's lower mantle (i.e., P = 0-160 GPa, V/V 0 = 0.65-1.00, T = 0-3000 K).…”
Section: P-v-t Equation Of State (Eos)mentioning
confidence: 99%
“…44,45 Meanwhile, FeO has been investigated by Fischer et al 7 and Richet et al 46 In the present study, the experimental results on MgO reported by Li et al 43 and FeO reported by Fischer et al 7 were selected as reference data to calculate the compressibility of (Mg 1−x Fe x )O ferropericlase. In the case of MgO, B 1 = 164(11) GPa, 43 dB 1 /dP = 4.2 43 and V 1 = 11.248 cm 3 /mol. 43 The corresponding values of the elastic parameters for FeO are B 2 = 150 GPa, 7 dB 1 /dP = 3.6 7 and V 2 = 12.256 cm 3 /mol.…”
Section: Application Of the Model To The (Mg 1−x Fe X ) Ferropermentioning
confidence: 99%
“…In the case of MgO, B 1 = 164(11) GPa, 43 dB 1 /dP = 4.2 43 and V 1 = 11.248 cm 3 /mol. 43 The corresponding values of the elastic parameters for FeO are B 2 = 150 GPa, 7 dB 1 /dP = 3.6 7 and V 2 = 12.256 cm 3 /mol. 7 The resultant bulk moduli of ferropericlase at the corresponding molar fraction x obtained by substituting the aforementioned elastic data into Eqs.…”
Section: Application Of the Model To The (Mg 1−x Fe X ) Ferropermentioning
confidence: 99%
See 1 more Smart Citation